2004
DOI: 10.1038/sj.bdj.4811800
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to improving the quality of referrals for potential oral cancer

Abstract: The quality and content of referral letters are important for prioritisation of patients who may have oral cancer. Referrals letters to the Oral Medicine Clinic at Birmingham Dental Hospital were analysed and practitioners interviewed. Whilst acceptable for general purposes, most letters did not contain sufficient information to allow effective prioritisation. Interviews disclosed a misunderstanding amongst practitioners about the way in which referrals were handled. A number of barriers to increasing the info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 7 publications
2
26
0
Order By: Relevance
“…10 Among 120 oral cancers diagnosed in a hospital setting, only 75% had an indication of a suspected malignancy. 10 White et al 11 speculated that a high proportion of dental practitioners were unaware of the mechanisms in place for urgent oral medicine referrals. The fi nding that only four of the letters suspecting a malignancy or giving features of a malignancy were received on a two-week wait cancer pro-forma suggest that improvements in communication on cancer referral guidelines by primary care trusts with local medical and dental practitioners is needed.…”
Section: Discussionmentioning
confidence: 99%
“…10 Among 120 oral cancers diagnosed in a hospital setting, only 75% had an indication of a suspected malignancy. 10 White et al 11 speculated that a high proportion of dental practitioners were unaware of the mechanisms in place for urgent oral medicine referrals. The fi nding that only four of the letters suspecting a malignancy or giving features of a malignancy were received on a two-week wait cancer pro-forma suggest that improvements in communication on cancer referral guidelines by primary care trusts with local medical and dental practitioners is needed.…”
Section: Discussionmentioning
confidence: 99%
“…9 In order to be useful, referral documents must provide organized information, rhetorical relevance, appropriate level of detail, and be concise. 12,14 However, several studies have reported that referral letters often lack important information, 7,8,9,10,12,13,15,16 which can result in problems such as improper scheduling, prioritization errors, 9,11,13 unnecessary repetition of tests 7 and, ultimately, inadequate care and delay in treating the illness. 10 Several studies aimed at defining the necessary information for the referral of patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,10,12,16,17 Depending on the specialty, the clinical description of the lesion is considered essential. 9,12,13,16 Lesion details may include type (primary morphology), 13,16 size, 9,16 location, 12,13,16 color and eventual ulceration, 9,13 shape and consistency, 9 thickness, texture, presence of rolled margin (in the case of oral squamous cell carcinoma), 13 duration, 12,16 symptoms, 12,16 clinical diagnosis, 12,16 suspicion of malignancy, 17 risk factors for disease, and management details, such as use of medications/mouthwash, previous biopsy or denture/tooth adjustment. 13 Specific strategies have been suggested to improve the content of referral documents, such as the use of support tools, 6,10,16 investment in education and training of professionals, 6,10 and the use of electronic referrals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations